Are neighboring trees in tune? Wood formation in Pinus pinaster - Vieira, Joana (2014)
Neighboring trees growing under identical environmental conditions can exhibit different dynamics and periods of growth. Despite the recent advances in cambial biology, the exogenous and endogenous factors generating asynchronous xylem growths still remain undetermined. This study investigated timings and duration of xylem formation in maritime pine (Pinus pinaster Ait.) from an even-aged plantation in Portugal growing under Mediterranean climate. Cambial phenology and stem diameter were monitored weekly, from March to December 2010, on two classes of trees divided according to the tree ring widths of the last 15 years, but similar age and size: fast- and slow-growing trees. We tested the hypothesis that differences in tree ring widths result from cell production which in turn affects timings of xylogenesis and that the bimodal growth pattern, typical of the Mediterranean, originates from a double reactivation of the cambium: in spring and autumn. Cambial activity started earlier and ended later in fast-growing trees, confirming that cell production is a key factor determining the duration of xylogenesis. Intra-annual variations in stem diameter recorded by band dendrometers revealed two peaks of increment occurring in spring and late summer. However, the number of cambial cells did not increase in late summer, which suggested that the second peak of increment was caused by stem rehydration, rather than by a reactivation of cell division. These results demonstrated that the variability in the timings of xylem phenology observed among trees of the same age and size and growing under similar environmental conditions was closely related to cell production and not to age or size per se.